Sales management : analysis and decision making - Ingram, Thomas N. (New York: Routledge, 2024)
"This eleventh edition of Sales Management continues the tradition of blending the most recent sales management research with the real-life "best practices" of leading sales organizations and sales professionals. Reflecting today's emphasis on analytics and customer experience (CX), this edition focuses on the importance of employing different data-based selling strategies for different customer groups, as well as integrating corporate, business, marketing, and sales-level strategies and plans. Sales Management includes coverage of the current trends and issues in sales management, along with real-world examples from the contemporary business world that are used throughout the text to illuminate chapter discussions. The new eleventh edition includes: Emphasis on data-driven decision making, ethics, the use of artificial intelligence, the customer experience, leadership, sales enablement technology and new communication technologies; Updated end-of-chapter cases with application questions and role plays, along with skill-building experiential exercises with discovery investigations and focused role plays, which place students in the role of sales manager; Updated ethical dilemmas for students to practice ethical decision making; Revised 'Sales Management in Action' boxes; Multiple vignettes embedded in each chapter featuring sales management professionals and well-known companies discussing key topics from that chapter. This text is core reading for postgraduate, MBA and executive education students studying Sales Management. An updated online instructor's manual with solutions to cases and exercises, revised test bank, and updated PowerPoints, is available to adopters"--
Includes bibliographical references (pages 323-340) and index.
Keywords: Sales management